ANALISIS EFISIENSI PASAR MODAL BENTUK SETENGAH KUAT - Noviarti; Melkisedek (Jurnal Manajemen, 2019)
The Purpose of This study to examine the efficiency of the half-strong form of capital market information with observing whether there are abnormal stock returns around dividend announcements, as well as the reaction speed of the capital market to dividend announcements. The company that has been studied is manufacturing sector companies listed on the Indonesian stock exchange for 4 years from 2014-2017. This type of research is event study. The research population is manufacturing companies listed on the Indonesia Stock Exchange. Samples that have been selected in this study were determined by purposive sampling method that is by several criteria. Of the 144 manufacturing companies totaling 118 not shared dividends as a whole, only 26 companies met the criteria as research samples. Based on the results of the study, it can be concluded that the Indonesian Capital Market is efficient in the form of half strong around the event of dividend announcements and has information content.This is indicated with the existence of a significant abnormal return on the seventh and first day (t-7 & t-1) before the event date and the fourth and eighth days after the event date (t + 4 and t + 8). at t-7 and t-1, indicates a leak of information about dividend announcements so that on the day of the announcement the market does not react significantly. On the fourth day (t + 4) investors can absorb new information. On the eighth day (t + 8) investors try to take advantage of profits, but the market quickly makes a balance so investors cannot use it to take advantage.